Mining of massive datasets - Leskovec, Jurij (Cambridge University Press, 2014)
This book focuses on practical algorithms that have been used to solve key problems in data mining and which can be used on even the largest datasets. It begins with a discussion of the map-reduce framework, an important tool for parallelizing algorithms automatically.